English Language Teaching in Islamic Education: A Bibliometric Analysis - Nurfazri, Muhammad; Sulaeman, Dedi; Ali, Hapid (Science, Tecnology, Religious, Economic, and Social Humanitis (STREAS), 2026)
The integration of English language teaching into Islamic education has expanded in response to global academic demands. However, comprehensive quantitative mapping of this field remains limited. This study aims to examine publication trends, intellectual structure, and thematic gaps in ELT within Islamic education. Using the Scopus database, the study analyzed 98 journal articles published between 2004 and 2026. Bibliometric analysis was performed with VOSviewer to explore keyword co occurrence, author collaboration networks, and citation patterns. The findings indicate a marked increase in research output after 2018. Indonesia appears as the leading contributor and an important center of international collaboration. Keyword co occurrence analysis shows a dominant focus on “English language teaching” and “Islamic education,” with increased attention to teachers’ roles and blended learning during the COVID 19 period. Citation analysis highlights key foundational studies and leading journals, including the Asian EFL Journal and Studies in English Language and Education, as central to the development of the field. The study also reveals thematic gaps in bilingualism, cultural schemas, teacher roles, competency-based curricula, technology integration, and the development of specialized instructional materials suited to the sociocultural context of Islamic institutions. These gaps provide clear directions for future research.